Customer Satisfaction on the Tangerang-Merak Toll Road: The Effects of Cashless Payments, Service Quality, and Loyalty - Masturi Masturi; Hamdan Hamdan (International Forum of Researchers and Lecturers, 2025)
This study investigates the impact of cashless payment technologies, specifically e-toll and Garda Total Objek (GTO), on customer satisfaction and travel efficiency on the Tangerang-Merak Toll Road. The research demonstrates that the implementation of these technologies significantly enhances travel time efficiency and overall user satisfaction, providing a more seamless and convenient toll payment experience. Despite these positive outcomes, the study identifies several technical challenges that hinder optimal performance. Notably, there is an 18% transaction failure rate, primarily caused by malfunctions in card reader devices and server disruptions, which negatively affect the customer experience. In addition to technological reliability, the quality of service delivered by field staff and the degree of customer loyalty emerge as critical factors influencing sustained use of the digital payment system and overall satisfaction levels.The study underscores the importance of time efficiency and customer loyalty as key drivers for improving service quality and encouraging the widespread adoption of cashless systems. To address these challenges, the study recommends enhancing the reliability of payment devices and network infrastructure through regular maintenance and upgrades. Furthermore, the adoption of Multi-Lane Free Flow (MLFF) technology is suggested to allow toll transactions without stopping, thereby reducing traffic congestion and waiting times at toll plazas. Continuous staff training is essential to improve service response and technical troubleshooting. Additionally, customer loyalty programs offering incentives like discounts and rewards could increase user engagement. The study also emphasizes the need for increased public education on cashless payment systems and their features to minimize resistance and misunderstandings. Finally, ongoing monitoring and evaluation based on user feedback are critical for promptly addressing issues and sustainably improving customer satisfaction.